Minilateralism and Great Power Competition during the COVID-19 Pandemic: A Case Study of Mekong Region - Jaknanihan, Arrizal Anugerah (Journal of Integrative International Relations, 2022)
Minilateral institutions such as Lancang-Mekong Cooperation and Lower Mekong Initiative have an indispensable role in channeling the influence of external powers to the Mekong region. This article analyzes the impact of US-China competition on minilateral institutions in the context of the COVID-19 pandemic. By using institutional balancing theory, this article explains the geopolitical and geoeconomic imperative behind the minilateral cooperation in Mekong during the pandemic. As the external powers compete for influence, the range of minilateral cooperation has expanded to solve the issues brought by the pandemic, especially health security and economic recovery. However, notwithstanding the assistance, Mekong countries remain steadfast in maintaining their autonomy. Regional powers such as Vietnam and Thailand did this by harnessing the intra-regional institution and diversifying their partners.